The antisocial personality disorder in the Brazilian movies - Honorato,Tabata Galindo (2018)
ABSTRACT Objective: The antisocial personality disorder (APD) is one theme of interest for psychiatry/mental health students and professionals. The access to psychopathology aspects by means of movies is able to improve the understanding about these disorders. This study aimed at evaluates the frequency of APD and of its diagnostic criteria in the Brazilian cinema for teaching purposes. Methods: The method consisted of survey sampling (for convenience, once the study is extracted from another greater project); use of a diagnostic instrument and analysis of the results. Results: 44.73% of the personalities were diagnosed with APD. All the diagnostic criteria for APD were present. The most frequent criterion was the practice of illegal acts. Impulsivity was associated with aggressiveness in 29.4% of the cases and with the use of psychoactive substances in almost 30% of the cases. 35.3% of the characters had a premature and violent death. Conclusion: The research enabled the identification of APD diagnostic criteria in the Brazilian cinema. Many scenes were able to represent the diagnosis clearly. The data proved to be sufficient in indicate the potentiality of the material as a didactic and pedagogical foundation.